Ultranarrow line width room-temperature single-photon source from perovskite quantum dot embedded in optical microcavity - Farrow, T; Dhawan, AR; Marshall, AR; Ghorbal, A; Son, W; Snaith, HJ; Smith, JM; Taylor, RA (American Chemical Society, 2023)
Ultranarrow bandwidth single-photon sources operating at room-temperature are of vital importance for viable optical quantum technologies at scale, including quantum key distribution, cloud-based quantum information processing networks, and quantum metrology. Here we show a room-temperature ultranarrow bandwidth single-photon source generating single-mode photons at a rate of 5 MHz based on an inorganic CsPbI3 perovskite quantum dot embedded in a tunable open-access optical microcavity. When coupled to an optical cavity mode, the quantum dot room-temperature emission becomes single-mode, and the spectrum narrows down to just ∼1 nm. The low numerical aperture of the optical cavities enables efficient collection of high-purity single-mode single-photon emission at room-temperature, offering promising performance for photonic and quantum technology applications. We measure 94% pure single-photon emission in a single-mode under pulsed and continuous-wave (CW) excitation.